Surgery for bilateral vocal fold paralysis: Systematic review and meta-analysis - Titulaer, Kai; Schlattmann, Peter; Guntinas-Lichius, Orlando (Frontiers in Surgery, 2022)
Objectives To determine the decannulation rate (DR) and revision surgery rate after surgery for bilateral vocal fold paralysis (BVFP). Data Sources Five databases (MEDLINE, PubMed, Embase, Web of Science, Scopus) were searched for the period 1908–2020. Methods The systematic literature review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were pooled using a random-mixed-effects model. Randomized controlled trials and non-randomized studies (case-control, cohort, and case series) were included to assess DR and revision surgery rate after different surgical techniques for treatment of BVFP. Results The search yielded 857 publications, of which 102 with 2802 patients were included. DR after different types of surgery was: arytenoid abduction (DR 0.93, 95%-confidence interval [CI], 0.86–0.97), endolaryngeal arytenoidectomy (DR 0.92, 95%-CI, 0.86–0.96), external arytenoidectomy (DR 0.94; 95%-CI, 0.71–0.99), external arytenoidectomy and lateralisation (DR 0.87; 95%-CI, 0.73–0.94), laterofixation (DR 0.95; 95%-CI, 0.91–0.97), posterior cordectomy (DR 0.97, 95%-CI, 0.94–0.99), posterior cordectomy and arytenoidectomy (DR 0.98, 95%-CI, 0.93–0.99), posterior cordectomy and subtotal arytenoidectomy (DR 0.98, 95%-CI, 0.88–1.00), posterior cordotomy (DR 0.96, 95%-CI, 0.84–0.99), reinnervation (0.69, 95%-CI, 0.12–0.97), subtotal arytenoidectomy (DR 1.00, 95%-CI, 0.00–1.00) and transverse cordotomy (DR 1.0, 95%-CI, 0.00–1.00). No significant difference between subgroups for DR could be found (Q = 15.67, df = 11, p = 0.1540). The between-study heterogeneity was low (τ2 = 2.2627; τ = 1.5042; I2 = 0.0%). Studies were at high risk of bias. Conclusion BLVP is a rare disease and the study quality is insufficient. The existing studies suggest a publication bias and the literature review revealed that there is a lack of prospective controlled studies. There is a lack of standardized measures that takes into account both speech quality and respiratory function and allows adequate comparison of surgical methods.